Macroscopic and histological features of placentas at 34-43 weeks' gestation and their association with infant admission to the neonatal unit. (18th April 2012) - Pathak, S; Sebire, NJ; Jessop, F; Murdoch, E; Hackett, GA; Lees, CC
Abstract : Objective: To define the morphological and histological characteristics in the placentas of infants admitted to the Neonatal Unit admitted at and/or near term compared to those not. Methods: In a prospective study, 1, 153 unselected women with singleton pregnancies, delivering at 34-43 weeks of gestation were recruited in a single UK maternity unit. Of those, sixty six infants required Neonatal Unit admission. Data on placental morphological indices and predefined histological lesions were analysed and compared for infants admitted and those not admitted to the Neonatal Unit. Results: There was no significant difference in the morphological indices cord coiling, cord centrality or cord eccentricity for placentas of infants admitted to the Neonatal Unit compared to those not admitted (Mean 0.20, 0.39, 0.53 versus 0.20, 0.36, 0.49 respectively). Histological features of ascending genital tract infection were more frequent in the placentas from infants admitted to the Neonatal Unit (18.8% versus 10.5%; p=0.04) compared to those not admitted. The frequency of all other predefined histological placental lesion was similar. Conclusions: These cases were drawn from a large unselected population as opposed to those placentas received for histopathological investigation based on clinical indication. There are no morphological differences between placentas where infants were admitted to the Neonatal Unit compared to those not admitted. The findings of this study do not support routine placental examination in all cases of neonatal admissions delivered at or near term.